LB Lamp Production Planning Based on Fuzzy Logic Approach at PT XYZ - Bayyinah, Aulia Nabil; Santosa, Sesar Husen (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Increasingly tight competition in the industrial market encourages companies to optimize production planning to meet customer demand efficiently. Effective production planning is key in achieving this goal, as it guides entities towards achieving their goals appropriately. This research aims to develop a fuzzy method for production planning at PT XYZ, a lamp manufacturing company. This method is designed to assist PT XYZ The approach used in this research includes historical data analysis, forecasting techniques using the time series method, calculating raw material inventory, and applying fuzzy logic to determine optimal production quantities. Based on the results of fuzzy calculations, the production amount for the next period of 7,000 product units can be a suggestion for companies to avoid production shortages and excesses due to uncertainty in product demand.